Endoscopic findings of gastric lesions in patients with eosinophilic gastrointestinal disorders - Fujiwara, Yasuhiro; Tanoue, Kojiro; Higashimori, Akira; Nishida, Yu; Maruyama, Masatsugu; Itani, Shigehiro; Ominami, Masaki; Nadatani, Yuji; Fukunaga, Shusei; Otani, Koji; Hosomi, Shuhei; Tanaka, Fumio; Kamata, Noriko; Nagami, Yasuaki; Taira, Koichi; Machida, Hirohisa; Tanigawa, Tetsuya; Watanabe, Toshio; Ohsawa, Masahiko; F-Study group (Endoscopy International Open, 2020)
Background and study aims Eosinophilic gastrointestinal disorders are classified into eosinophilic esophagitis, eosinophilic gastritis, eosinophilic gastroenteritis, and eosinophilic colitis according to the site of eosinophilic infiltration. Although well established in eosinophilic esophagitis, endoscopic findings in eosinophilic gastritis and eosinophilic gastroenteritis with regard to gastric lesions have not been clearly described. The aim of this study was to identify endoscopic findings of gastric lesions associated with eosinophilic gastrointestinal disorders.Patients and methods Out of 278 patients with eosinophilic gastrointestinal disorders, 18 had eosinophilic gastritis or eosinophilic gastroenteritis confirmed by biopsy; their endoscopic images were analyzed retrospectively. The association between endoscopic findings and number of eosinophils in the gastric mucosa was investigated.Results Erythema was most frequently observed (72 %), followed by ulcers (39 %), discoloration (33 %), erosions (28 %), nodularity (28 %), and polyps (28 %). There were several unique endoscopic findings such as submucosal tumor-like deep large ulcers in three patients, antral Penthorum-like appearances (small nodules radially lined toward the pyloric ring) in three patients, “muskmelon-like appearances” (discolored mucosa-composed mesh pattern) in three patients, multiple white granular elevations in two patients, cracks (appearance of furrows similar to those in eosinophilic esophagitis) in five patients, and antral rings in one patient. No significant association was observed between endoscopic findings and number of gastric eosinophils.Conclusions Several unique endoscopic findings of gastric lesions were observed in patients with eosinophilic gastritis or eosinophilic gastroenteritis. Submucosal tumor-like ulcers, antral Penthorum-like appearances, muskmelon-like appearances, and cracks might be associated with eosinophilic gastrointestinal disorders.